Peningkatan Pengetahuan Peran Guru, Uks, dan Pedagang Jajanan Sekolah Dasar dalam Menyediakan Makanan Bergizi - Desri Suryani; Tonny Cortis Maigoda; Yunita Yunita; Meriwati Meriwati (Universitas Malahayati Lampung, 2026)
ABSTRACT A common problem in elementary school cafeterias is that snacks do not meet balanced nutritional and food safety standards, such as high sugar, salt, and fat content, the use of artificial colors and preservatives, coupled with poor sanitation and hygiene, as well as a lack of knowledge and supervision from teachers, school health unit (UKS) managers, and vendors. The objective of this community service project is to enhance the capacity of these three parties to provide food that is safe, nutritious, and meets health standards. The methods used included interactive lectures, Focus Group Discussions (FGDs), practical workshops on developing healthy menus, serving simulations, and on-site mentoring. The community service partners were teachers, school health unit (UKS) managers, and snack vendors at SDN 71 in Bengkulu City, totaling 17 participants. Evaluation was conducted using pre- and post-tests. The results of the community service program showed an increase in knowledge following the intervention, which consisted of training, discussions, and hands-on practice. The average knowledge score increased from 92.94 to 97.94 Keywords: Healthy Canteen, Balanced Nutrition, Food Safety, Teachers, Elementary School. ABSTRAK Masalah umum di kantin sekolah dasar adalah jajanan yang tidak sesuai standar gizi seimbang dan keamanan pangan, seperti kadar gula, garam, dan lemak tinggi, penggunaan pewarna serta pengawet buatan, ditambah higiene sanitasi buruk serta minimnya pengetahuan dan pengawasan dari guru, pengelola UKS, maupun pedagang. Tujuan pengabdian ini adalah meningkatkan kapasitas ketiga pihak tersebut dalam menyediakan makanan aman, bergizi, dan memenuhi standar kesehatan. Metode yang digunakan meliputi ceramah interaktif, Focus Group Discussion (FGD), workshop praktik penyusunan menu sehat, simulasi penyajian, dan pendampingan lapangan. Mitra pengabdian adalah guru, pengelola UKS, dan pedagang jajanan di SDN 71 Kota Bengkulu sebanyak 17 peserta. Evaluasi menggunakan pretest dan posttest. Hasil pengabdian menunjukkan peningkatan pengetahuan setelah intervensi berupa pelatihan, diskusi, dan praktik langsung. Rata-rata nilai pengetahuan meningkat dari 92,94 menjadi 97,94. Kata Kunci: Kantin Sehat, Gizi Seimbang, Keamanan Pangan, Guru, Sekolah Dasar.